Chair Versus Chairman: Does Orthopaedics Use the Gendered Term More Than Other Specialties? - Peck, Connor J. (Clin Orthop Relat Res, 2020)
BACKGROUND: Orthopaedics is the least gender-diverse medical specialty. Research suggests that the use of gendered language can contribute to workforce disparity and that gender-neutral language supports the inclusion and advancement of women, but the degree to which gender-neutral language is used by academic departments in what typically is a department’s highest position (department chair) has not been characterized. QUESTIONS/PURPOSES: (1) Is the proportion of department websites that use the term chairman (as opposed to chair) greater in orthopaedics than in five other surgical and medical specialties? (2) Are departments led by chairs who are women less likely to use “chairman” than those led by men, and does this vary by specialty? METHODS: Seven hundred fourteen official websites of orthopaedic, neurosurgery, general surgery, internal medicine, pediatrics, and obstetrics and gynecology departments affiliated with 129 allopathic medical schools were screened. Any use of the term chairman on title pages, welcome messages, and faculty profile pages was identified using a Boyer-Moore string-search algorithm and terms were classified based on their location on the site. The overall use of the term chairman was compared by specialty and gender of the chair. RESULTS: Sixty percent of orthopaedic department websites (71 of 119) used the term chairman at least once, a proportion higher than that of pediatrics (36% [46 of 128]; OR 0.38; 95% CI, 0.23 to 0.63; p < 0.001), internal medicine (31% [38 of 122]; OR 0.030; 95% CI, 0.18 to 0.53; p < 0.001), and obstetrics and gynecology (29% [37 of 126]; OR 0.28; 95% CI, 0.17 to 0.48; p < 0.001), but no different than that of neurosurgery (57% [54 of 94]; OR 0.91; 95% CI, 0.52 to 1.6; p = 0.74) and general surgery (55% [69 of 125]; OR 0.83; 95% CI, 0.50 to 1.4; p = 0.48). Across disciplines, departments whose chairs were women were much less likely to use the term chairman than departments whose chairs were men (14% [17 of 122] versus 50% [297 of 592]; OR 0.16; 95% CI, 0.09 to 0.28; p < 0.001). CONCLUSIONS: The frequent use of the term chairman in orthopaedics, coupled with the preference of women to use the term chair, suggests considerable room for growth in the use of gender-equal language in orthopaedics. CLINICAL RELEVANCE: Our current efforts to increase the number of women in orthopaedics may be undermined by gendered language, which can create and reinforce gendered culture in the field. Electing to use gender-neutral leadership titles, while a relatively small step in the pursuit of a more gender-equal environment, presents an immediate and no-cost way to support a more inclusive culture and counteract unconscious gender bias. Future studies should explore the individual attitudes of chairs regarding the use of gendered titles and identify additional ways in which biases may manifest; for example, the use of gendered language in interpersonal communications and the presence of unconscious bias in leadership evaluations. Continued efforts to understand implicit bias in orthopaedics can guide actionable strategies for counteracting gendered stereotypes of the specialty, in turn aiding initiatives to recruit and promote women in the field.